Selective Anthelmintic Treatment at Different Physiological Stages in Hair Sheep Under Humid Tropical Conditions - Luna-Palomera, C.; Sanchez -Dávila, F.; González-Garduño, R.; Domínguez-Viveros, J.; Ojeda-Robertos, N. F.; Maldonado García, N. M. (Tropical Animal Science Journal, 2025)
Ewes’ genotype and physiological stage are important factors associated with gastrointestinal nematode infection. The aims were to evaluate the parasitic (fecal eggs count, FEC), health (anemia level, FAMACHA; packed cell volume, PCV; hemoglobin, HGB), and productive response (live weight, LW; body condition score, BCS) of hair ewes managed under a selective deworming program with levamisole (7.5 mg/kg of live weight) at reproductive stages (not pregnant, NPW, n=17; ewes between the first and second third of gestation, 1-3PW, n=22; ewes in the last third of gestation and peripartum, 4-5PWN, n=16) and genotype groups (Pelibuey, PB, n=12; Katahdin, KT, n=12; Pelibuey × Katahdin, F1 PB×KT, n=16; and Pelibuey × Dorper F1 PB×DP, n=15). The effects of treatments were studied using analysis of variance, considering the reproductive stages and genotypes as treatments through 4 evaluation periods (days 20, 48, 76, and 104). FEC values were higher (p<0.01) for ewes at 4-5PW than 1-3PW and NPW. FAMACHA, PCV, LW, and BCS were similar in ewes regardless of the reproductive stage. On day 48 post-deworming (levamisole at 7.5 mg/kg of LW), the proportion of ewes with >800 e/g was higher (13.74%) at 4-5PW than at the peripartum stage. On day 76, the accumulated proportion of ewes that were dewormed was higher (p<0.05) at 4-5PW than at the peripartum stage. The accumulated total proportion revealed that the genotype F1 PB×DP ewes had the highest deworming requirement (p<0.05), being dewormed at least once (32.8%). According to the indicators of LW, BCS, FAMACHA, FEC, PCV, HGB, and proportion of dewormed animals, ewes with the F1 PB×KT genotype showed the best performance. Therefore, reproductive stage-orientated management and the use of the best genotype for grazing conditions combined with a selective deworming program can contribute significantly to the control of gastrointestinal nematodes.